Srategi Pembelajaran Pendidikan Agama Islam Pada Anak Usia Dini - Guswita, Mela; Ru'iya, Sutipyo (Akhlaqul Karimah: Jurnal Pendidikan Agama Islam, 2024)
Children are a mandate from Allah SWT which is the responsibility of parents. Education is one of the responsibilities carried out so that the child's nature is well maintained. To maintain this nature, early childhood education is very important so that children become religious and akhlakul karimah (noble character). This article aims to describe learning strategies for Islamic religious education in early childhood. This study uses a qualitative method, namely research that produces descriptive data in the form of written or oral explanations from people, the behavior observed in the learning process of Islamic Religious Education in Early Childhood. This study uses a phenomenon approach in early childhood learning strategies at the Sleman Mother's House, Yogyakarta. Data collection techniques in this study used observation, interviews, and documentation obtained from sources related to research, such as books, journals, scientific papers, school profiles, and photos of learning activities that can support research data. While the data analysis technique uses data reduction, data presentation, conclusion drawing, and data validation. The results showed that the strategies used in learning at the Sleman Mother's House in Yogyakarta were telling stories, demonstrations, singing, exemplary, habituation, or playing exercises (Sentra). At Sentra (Beyond center time and circles), children are exposed to various cognitive, motor, and sensory aspects; These three aspects contain Islamic religious values that can be carried out in playing activities so that they become habituation in everyday life.